Pengaruh Sikap Keuangan terhadap Pengambilan Keputusan dalam Mengelola Modal Usaha Pada Pelaku UMKM di Surabaya Food Street (Gaza) - Nur N; Veronika Febriyana Roju; Istiono I (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the influence of financial attitude on decision-making in managing business capital among micro, small, and medium enterprise (MSME) entrepreneurs at Surabaya Food Street (GAZA), Universitas 17 Agustus 1945 Surabaya. A quantitative causal-associative research design was employed, with a sample of 12 respondents selected through purposive sampling. Data were collected using a closed-ended questionnaire with a five-point Likert scale, and analyzed using simple linear regression. Prior to regression analysis, validity, reliability, and classical assumption tests were conducted. The results indicate that all measurement items were valid (r-count r-table = 0.576) and the instrument was highly reliable (Cronbach's Alpha = 0.915). Classical assumption tests confirmed that the data were normally distributed (Shapiro-Wilk sig. 0.05), free from heteroscedasticity (Glejser sig. = 0.314 0.05), and exhibited a linear relationship (Deviation from Linearity sig. = 0.366 0.05). The regression equation obtained was Y = 31.334 + 0.288X, with a coefficient of determination (R²) of 0.146, indicating that financial attitude explains 14.6% of the variation in business capital decision-making. The t-test result (t = 1.309, sig. = 0.220 0.05) shows that financial attitude does not have a statistically significant effect on business capital decision-making at the 5% significance level, leading to the rejection of Hypothesis 1 (H?). This non-significant result is likely attributable to the small sample size (n = 12), which limits statistical power.